Dibromido(2,3-di-2-pyridylpyrazine-κ(2) N (1),N (2))platinum(II) - Ha, Kwang (International Union of Crystallography, 2011)
The Pt(II) ion in the title complex, [PtBr(2)(C(14)H(10)N(4))], is four-coordinated in a distorted square-planar environment by two N atoms of a chelating 2,3-di-2-pyridylpyrazine ligand and two bromide anions. In the crystal, the pyridyl ring coordinated to the Pt atom is inclined slightly to its carrier pyrazine ring [dihedral angle = 14.7 (2)°], whereas the uncoordinated pyridyl ring is inclined considerably to the pyrazine ring [dihedral angle = 51.9 (3)°]. The dihedral angle between the two pyridyl rings is 57.7 (3)°. Two complex molecules are assembled through intermolecular C—H⋯N hydrogen bonds, forming a dimer-type species. Intramolecular C—H⋯Br and C—H⋯N hydrogen bonds are also present.